Prosthetic Oral Rehabilitation with CAD/CAM Suprastructures in Patients with Severe Tissue Deficits: A Case Series - Marisa Laurila; Pilvi Mäntynen; Jari Mauno; Juho Suojanen (MDPI AG, 2023)
This article presents the outcomes of prosthetic oral rehabilitation using CAD/CAM telescopic bar overdentures in patients with oral cancer (n = 3), severe facial trauma (n = 2), or various syndromes (n = 1), all suffering from severe tissue deficits and requiring complex and comprehensive oral rehabilitation. The aim was to assess the durability and functionality of implant-retained prosthetic structures, ensuring easy oral hygiene and minimizing specialized follow-up needs. The data for this study were sourced from a retrospective cohort at Helsinki University Hospital. The prosthetic reconstruction encompassed the Atlantis 2in1 and the Createch removable telescopic systems. Thus, 40 implants were placed (4 to 7 per patient), with prosthetic structures in the maxilla (n = 4 patients), in the mandible (n = 1), and in both jaws (n = 1). Two patients experienced no complications, two patients had part of the acrylic resin break, and one patient experienced loosening of the bar structure. All complications associated with prosthetic structures were successfully managed, and none of the implants were lost. The follow-up time ranged from 7 to 126 months. This rehabilitation is proved to be an effective solution for patients with complex oral conditions, facilitating both functional restoration and ease of maintenance. These findings underscore the importance of individualized treatment approaches in cases of tissue deficits.